2005
DOI: 10.1021/ja045670+
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Dispersions of Single-wall and Multiwall Carbon Nanotubes with Designed Amphiphilic Polycations

Abstract: Poor solubility of single-walled and multiwalled carbon nanotubes (NTs) in water and organic solvents presents a considerable challenge for their purification and applications. Macromolecules can be convenient solubilizing agents for NTs and a structural element of composite materials for them. Several block copolymers with different chemical functionalities of the side groups were tested for the preparation of aqueous NT dispersions. Poly(N-cetyl-4-vinylpyridinium bromide-co-N-ethyl-4-vinylpyridinium bromide-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
295
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(312 citation statements)
references
References 82 publications
15
295
2
Order By: Relevance
“…Furthermore, an increase in the I D /I G ratio for MWCNTs/ NR-latex was also observed as a consequence of the wrapping process by isoprene monomers in the NRlatex [45]. We confirmed that the surfactant treatments used in this study did not disturb the π-systems of the MWCNTs in the nanocomposites.…”
Section: 94×10supporting
confidence: 80%
“…Furthermore, an increase in the I D /I G ratio for MWCNTs/ NR-latex was also observed as a consequence of the wrapping process by isoprene monomers in the NRlatex [45]. We confirmed that the surfactant treatments used in this study did not disturb the π-systems of the MWCNTs in the nanocomposites.…”
Section: 94×10supporting
confidence: 80%
“…But most applications require well-dispersed SWNT systems in order to take advantage of the unique properties. Many surfactants such as lipids, sugars, proteins, DNA, commodity polymers, and designed polymers have been used to facilitate the dispersion of SWNTs [20][21][22][23][24][25][26]. Given the amphiphilicity of YK20, we examined the SWNT dispersing properties of YK20 in solution.…”
Section: Yk20 Assisted Dispersion Of Swntsmentioning
confidence: 99%
“…Up to now, three methods have been used to prepare liquid crystalline CNTs: acid oxidation [24,25], polymer wrapping [26][27][28][29], and superacid protonation [30,31]. Acid oxidation is an efficient method of modifying the CNT surface by introducing functional groups [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%